Metaverse Meets Branding: Examining Consumer Responses to Immersive Brand Experiences - Wongkitrungrueng, Apiradee; Suprawan, Lokweetpun (International journal of human-computer interaction, 2024)
The metaverse connects the physical and digital worlds to improve the consumer experience, but little is known about how consumers respond to branded virtual worlds in real life. This study proposes a model to investigate the influence of metaverse experiential value on consumer's brand perception and behavioral responses in the virtual and real world. The covariance-based SEM analysis was conducted based on data from 702 Thai users of Asia's largest metaverse platform. Results revealed that all three dimensions of value indirectly affect consumer-brand engagement (CBE) through brand image and virtual purchase intention. Hedonic value had no direct effect on consumer responses, but on symbolic and utilitarian value which in turn influences CBE and virtual purchase respectively. As one of the first empirical studies on metaverse brand experience, this study contributed by incorporating multidimensional and interrelated experiential value and examining the mediating role of brand image and virtual purchase. The findings suggest brand design the branded virtual environment to facilitate consumer learning and virtual ownership, and align virtual merchandise and store ambiance with the real world to unify the brand image in both worlds.